Tatei Watu (Our Father): A Tribute to Venâncio Mbande - Zango, Matchume (College of Music, 2023)
TATEI WATU (Our Father): Tribute to Venâncio Mbande is a creative project that culminated in the production of a CD Album in which thirteen musicians participated in the recording of musical arrangements inspired by the music of Mozambican composer Venâncio Mbande, a master of the traditional Chopi timbila xylophone style known as ngodo, who passed away in 2015. The CD album consists of eight musical tracks based on original material usually played in open outdoor spaces in the context of community celebrations and in an environment that is very different from the one in which we generally enjoy music today. The aim of my project was to bring this music to a modern audience that prefers listening to music on audio devices by means of new arrangements that rework the old ngodo pieces of Venâncio Mbande in a format and style that is within the reach of younger generations of listeners. This musical end result of the project is presented along with a short documentary on its creation, a folder of pre-mastering phase audio-samples and a dissertation that provides background, both on the CD's production and on the music's historical context. Through the prism of my own personal experience as a Chopi timbila performer, the creative project argues for a renewed relationship with older musical traditions of Africa and demonstrates by example that it is possible to engage with vanishing musics through the creation of musical works that are rooted in the traditional, yet contemporary in outlook.